Language Kinship of English, German, and Dutch: A Comparative Historical Linguistic Study - Nisa Anggraini Batubara; Dwi Widayati (CV. AFDIFAL MAJU BERKAH, 2022)
English, German, and Dutch belong to the Indo-European language family and the Germanic language subgroup. So there is an assumption regarding the existence of kinship of these three languages, which also could be seen in the fact that there are some similarities in the form and meaning. This makes the researchers analyze how the relationship between English, German, and Dutch is and how far the level of kinship of the three languages ​​is. This research is a quantitative research using qualitative descriptive method and lexicostatistical technique. Lexicostatistics is a technique in grouping languages ​​that tends to prioritize statistical observation of words (lexicon), and then tries to determine the grouping based on the percentage of similarities and differences between one language and another. By using 200 Swadesh’s basic vocabulary as an analytical material, 4 identical data and 102 similar data were found. The results of lexicostatistical calculations showed that the percentage of kinship of English (BI), German (BJ), and Dutch (BB) is 53%. From this calculation, it is determined that the linguistic status of these three languages is classified as languages ​​of the family.